2018
DOI: 10.1096/fj.201701377r
|View full text |Cite
|
Sign up to set email alerts
|

The fifth subunit in α3β4 nicotinic receptor is more than an accessory subunit

Abstract: The α3β4 subtype is the predominant neuronal nicotinic acetylcholine receptor present in the sensory and autonomic ganglia and in a subpopulation of brain neurons. This subtype can form pentameric receptors with either 2 or 3 β4 subunits that have different pharmacologic and functional properties. To further investigate the role of the fifth subunit, we coexpressed a dimeric construct coding for a single polypeptide containing the β4 and α3 subunit sequences, with different monomeric subunits. With this strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 55 publications
1
15
1
Order By: Relevance
“…Our conclusions are also at odds with a recent report showing that ( α 3) 2 ( β 4) 3 , but not ( α 3) 3 ( β 4) 2 or ( α 3) 2 ( β 4) 2 α 5 receptors, are efficiently expressed in the plasma membrane of transiently transfected normal rat kidney cells (Crespi et al. ). Whereas ( α 3) 3 ( β 4) 2 receptors are retained in the endoplasmic reticulum because of the missing third β 4 subunit carrying a LXM export motif, this motif is present in the α 5 subunit.…”
Section: Discussioncontrasting
confidence: 99%
“…Our conclusions are also at odds with a recent report showing that ( α 3) 2 ( β 4) 3 , but not ( α 3) 3 ( β 4) 2 or ( α 3) 2 ( β 4) 2 α 5 receptors, are efficiently expressed in the plasma membrane of transiently transfected normal rat kidney cells (Crespi et al. ). Whereas ( α 3) 3 ( β 4) 2 receptors are retained in the endoplasmic reticulum because of the missing third β 4 subunit carrying a LXM export motif, this motif is present in the α 5 subunit.…”
Section: Discussioncontrasting
confidence: 99%
“…First, our findings suggest that the retention motifs help prevent surface expression of unassembled or incorrectly assembled receptor subunits that escape the ER quality control mechanisms. The presence of an additional quality control checkpoint at the Golgi complex has been documented in many systems (Arvan et al, 2002;MacGurn et al, 2012), and some studies have suggested such a checkpoint exists in AChR trafficking to the cell surface (Keller et al, 2001;Zhao et al, 2009;Rezvani et al, 2010;Crespi et al, 2018). The Golgi-resident protein that binds the β/δ motifs remains unknown, but is likely distinct from known proteins such as unc-50 or VILIP which both promote Golgi to surface trafficking of the receptor (Eimer et al, 2007;Zhao et al, 2009).…”
Section: Function and Mechanism Of Mx-helix Signalsmentioning
confidence: 99%
“…Strikingly different results were obtained in rat kidney cells cotransfected with a dimeric plasmid expressing α3β4 together with a plasmid expressing α3, β4, or α5 (Crespi et al, 2018b). Using this approach, the authors found that including the β4-expressing construct resulted in (α3β4) 2 β4 receptors that reached the plasma membrane; in contrast, combining the dimeric construct with α3 resulted in (α3β4) 2 α3 receptors that failed to exit the endoplasmic reticulum, and combining the dimeric construct with α5 resulted in (α3β4) 2 α5 receptors were unable to exit the Golgi apparatus and were shuttled back to the endoplasmic reticulum (Crespi et al, 2018b).…”
Section: Receptor Expression and Membrane Traffickingmentioning
confidence: 85%
“…For their experiments, the authors inserted an N-terminal HA, cMYC, and V5 tag in the α3, β4, and α5 subunits, respectively, finding that 98% of receptors were (α3β4) 2 β4 receptors in cells expressing α3 and β4, whereas 50% of the receptors were (α3β4) 2 β4 and 50% were (α3β4) 2 α5 receptors in cells expressing α3, β4, and α5 subunits (Ray et al, 2017). Strikingly different results were obtained in rat kidney cells cotransfected with a dimeric plasmid expressing α3β4 together with a plasmid expressing α3, β4, or α5 (Crespi et al, 2018b). Using this approach, the authors found that including the β4-expressing construct resulted in (α3β4) 2 β4 receptors that reached the plasma membrane; in contrast, combining the dimeric construct with α3 resulted in (α3β4) 2 α3 receptors that failed to exit the endoplasmic reticulum, and combining the dimeric construct with α5 resulted in (α3β4) 2 α5 receptors were unable to exit the Golgi apparatus and were shuttled back to the endoplasmic reticulum (Crespi et al, 2018b).…”
Section: Receptor Expression and Membrane Traffickingmentioning
confidence: 90%